216k views
1 vote
Find the seventh term of the expansion

Please select the best answer from the choices provided

A
B
C
D

Find the seventh term of the expansion Please select the best answer from the choices-example-1
User Wulong
by
5.1k points

2 Answers

2 votes

Answer:


462 (3x)^5 (7y)^6

Explanation:

We are given the following expression to be expanded and we are to find its seventh term:


(-3x-2y)^(11)

The coefficient here is taken from Pascal's triangle (nCr on the calculator).

For the expansion, the power of the first term decreases by one each time while it increases for the latter term.


C^(11)_(7-1)=(11!)/(6!(11-6)!) = (6!.7.8.9.10.11)/(6!.1.2.3.4.5) = 462

Therefore, the seventh term of the expansion of
(-3x-2y)^(11) is
462(-3x)^5(-2y)^6

User Wezzy
by
5.4k points
5 votes

Answer:

Correct choice is A

Explanation:

The i-th term of the binomial expansion
\left(-3x-2y\right)^(11) is


T_i=C^(11)_(i-1)\cdot \left(-3x\right)^(11+1-i)\cdot (-2y)^(i-1).

If i=7, then


T_7=C^(11)_(7-1)\cdot \left(-3x\right)^(11+1-7)\cdot (-2y)^(7-1)=C^(11)_6\cdot (-3x)^5\cdot (-2y)^6=462\cdot (-3x)^5\cdot (-2y)^6.

Note that


C_6^(11)=(11!)/(6!(11-6)!)=(6!\cdot 7\cdot 8\cdot 9\cdot 10\cdot 11)/(6!\cdot 1\cdot 2\cdot 3\cdot 4\cdot 5)=462.

User Prakhar Varshney
by
6.0k points